1998
DOI: 10.1126/science.280.5363.596
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interaction of an Axin Homolog, Conductin, with β-Catenin, APC, and GSK3β

Abstract: Control of stability of beta-catenin is central in the wnt signaling pathway. Here, the protein conductin was found to form a complex with both beta-catenin and the tumor suppressor gene product adenomatous polyposis coli (APC). Conductin induced beta-catenin degradation, whereas mutants of conductin that were deficient in complex formation stabilized beta-catenin. Fragments of APC that contained a conductin-binding domain also blocked beta-catenin degradation. Thus, conductin is a component of the multiprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
1,009
1
6

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,160 publications
(1,034 citation statements)
references
References 23 publications
18
1,009
1
6
Order By: Relevance
“…Moreover, we have shown that the regulators of G protein signaling (RGS) domain of rAxin interacts directly with APC, and that expression of rAxin in COS or SW480 cells stimulates the degradation of b-catenin (Kishida et al, , 1999a. Several groups have also reported the similar results (Behrens et al, 1998;Hart et al, 1998;Itoh et al, 1998;Sakanaka et al, 1998;Hamada et al, 1999). Therefore, it appears that Axin downregulates bcatenin by binding to GSK-3b, b-catenin, and APC, and enhancing GSK-3b-dependent phosphorylation of b-catenin.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Moreover, we have shown that the regulators of G protein signaling (RGS) domain of rAxin interacts directly with APC, and that expression of rAxin in COS or SW480 cells stimulates the degradation of b-catenin (Kishida et al, , 1999a. Several groups have also reported the similar results (Behrens et al, 1998;Hart et al, 1998;Itoh et al, 1998;Sakanaka et al, 1998;Hamada et al, 1999). Therefore, it appears that Axin downregulates bcatenin by binding to GSK-3b, b-catenin, and APC, and enhancing GSK-3b-dependent phosphorylation of b-catenin.…”
Section: Introductionmentioning
confidence: 53%
“…Axil has 44% amino acid identity with rAxin and inhibits Xwnt-8-induced axis formation of Xenopus embryos like Axin . Conductin has been identi®ed as a b-catenin binding protein (Behrens et al, 1998) and found to be identical with Axil. We have found that both Axin and Axil bind to not only GSK-3b but also b-catenin directly, and that they promote GSK-3b-dependent phosphorylation of b-catenin .…”
Section: Introductionmentioning
confidence: 99%
“…Wnt-1 has been shown to regulate free pools of catenin (Papko et al, 1996) and both axin and the axin homologue conductin have been reported to alter b-catenin activity through interaction with Apc, b-catenin and GSK3b (Behrens et al, 1998;Ikeda et al, 1998;Kishida et al, 1998). The potential relevance of increased levels of b-catenin becomes clear in the light of ®ndings which show that b-catenin functionally interacts with and activates members of the Tcf family of DNA binding transcription factors, including both Lef-1 and Tcf 4 (Behrens et al, 1998;Korinek et al, 1997). Activation of transcriptional signalling by b-catenin-Tcf complexes has been shown to occur as a consequence of mutations in both Apc and b-catenin Rubinfeld et al, 1997) and mutations of bcatenin have been reported in human colorectal cancers (Sparks et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, cyclin D1 and c-Myc have been reported to act as downstream targets of ␤-catenin and stimulate cell proliferation. In the absence of Wnt signals, the cellular concentration of ␤-catenin is kept relatively low through interactions with other proteins, such as adenomatous polyposis coli (APC) protein (5), GSK3␤ (6) and axin (7), that are involved in the phosphorylation of ␤-catenin. This phosphorylated form of ␤-catenin is degraded by the ubiquitinproteasome system (8; Fig.…”
mentioning
confidence: 99%